Disciplinary Differences of Topical Progression in Discourse: The Case of Abstracts in Applied Linguistics and Literary Studies - Kövér, Ármin (Working Papers in Language Pedagogy, 2018)
Conducting research and successfully communicating research findings play an important part in the life of academic researchers and university students. Writing a publishable quality article can be exceptionally challenging for novice researchers and university students alike. However, if scholars want to become part of the discourse community in their research field, they should become familiar with the genre requirements of their discipline. It is especially important for them to be able to write an appropriate abstract because it can promote the research article. To help the novice researchers of English Literature and English Applied Linguistics gain an insight into the main features of a successful research article abstract, the present study analysed the topical structures of 10 Applied Linguistics and 10 Literary Studies abstracts, which were published in two prestigious journals of their respective fields. The outcomes of the study attempt to provide guidelines for both university students and novice researchers who would like to publish their works in English language academic journals.